2017
DOI: 10.1027/1016-9040/a000278
|View full text |Cite
|
Sign up to set email alerts
|

Unique and Shared Relationship Benefits of Consensually Non-Monogamous and Monogamous Relationships

Abstract: Abstract. The increased media and public curiosity on the topic of consensual non-monogamy (CNM) presents an interesting case, given that these types of relationships are highly stigmatized. In the present review piece, we first situate common themes of benefits that people believe are afforded to them by their CNM relationships within the current state of the literature to provide insight into unique and shared (with monogamy) relationship benefits. This approach helps uncover relationship benefits and theore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
91
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(105 citation statements)
references
References 82 publications
8
91
0
6
Order By: Relevance
“…Perhaps the most obvious of these contexts is the relationship status or relational label of the couple. Marital, cohabiting, casual, or non-monogamous relationships have been shown to have slightly differing processes and outcomes (Moors, Matsick, & Schechinger, 2017). In particular, sexual behavior, attitudes and processes have also been shown to differ based on relationship status (Herbenick et al, 2010), suggesting that differing statuses may be important to consider when exploring pornography.…”
Section: Relational Contextmentioning
confidence: 99%
“…Perhaps the most obvious of these contexts is the relationship status or relational label of the couple. Marital, cohabiting, casual, or non-monogamous relationships have been shown to have slightly differing processes and outcomes (Moors, Matsick, & Schechinger, 2017). In particular, sexual behavior, attitudes and processes have also been shown to differ based on relationship status (Herbenick et al, 2010), suggesting that differing statuses may be important to consider when exploring pornography.…”
Section: Relational Contextmentioning
confidence: 99%
“…Grunt-Mejer & Campbell, 2016;Moors, Matsick, Ziegler, Rubin, & Conley, 2013;Thompson, Bagley, & Moore, 2018). However, a small but growing body of empirical evidence suggests the contrary and also supports the notion that CNM relationships are equally viable options to monogamy (see Brewster et al, 2017;Conley, Matsick, Moors, & Ziegler, 2017;Moors, Matsick, & Schechinger, 2017;Rubel & Bogaert, 2015 for reviews and metaanalyses). Across several studies, researchers have found that people engaged in CNM and monogamy report similar levels of satisfaction, trust, commitment, and mental stability (e.g., Conley et al, 2017;Rubel & Bogaert, 2015).…”
Section: Public Health Significance Statementmentioning
confidence: 96%
“…Recent qualitative research with people in CNM relationships found that the most cited benefit of CNM reported by 42% of the sample) was diversified need fulfillment (54). In fact, in a study that followed people who were considering opening up an existing relationship found that one reason people seek out additional partners is to meet needs that are unfulfilled in their current relationships (55).…”
Section: Broadening Our Understanding Of Need Fulfillmentmentioning
confidence: 99%